Opera omnia Desiderii Erasmi Roterodami Ordinis Quarti Tomus Tertius - Miller, Clarence H. (Huygens instituut/Brill, 1979)
The ninth volume of the new edition of the Opera omnia of Erasmus is the third tome of the fourth ordo 'moralia continens' and entirely devoted to the edition of the Moriae encomium by Clarence H. Miller. It was Erasmus' own wish that the Moriae encomium should be published under this 'ordo'; v. Ep. I to Botzheim, 30 January 15 2 3, p. 40, II. 9-10; and Ep. 2283 to Boece, 15 March 1530, 1. 1°4. For the editorial principles of the new Erasmus edition we refer the reader to the General introduction of volume 1,1 and to the Prefaces of the other volumes published until now. To our deep regret we have to report the death of Professor S. L. Greenslade, a member ofthe 'Conseil International', and of Professor Myron P. Gilmore. The passing away of these eminent scholars and devoted friends of our new edition is a heavy loss to our project. As new members of the 'Conseil International' were elected C. Augustijn, Amsterdam, Ch. Bene, Grenoble, V. Branca, Venice, Mrs. M. Cytowska, Warsaw, F. Heinimann, Basle. The editorial board was also enlarged; the new membres are: C. L. Heesakkers, Leyden, H. J. de Jonge, Leyden, J. Trapman, The Hague Ooint-Secretary). The editorial board and the editor of the present volume thank all libraries who put books, photostats, microfilms and bibliographical material at their disposal. Referring to the copyright notice on the verso of the title page, and to the agreements made with the authors, the editorial board feels bound to repeat that no part of the volumes which have appeared or will appear under its responsibility can be published without prior permission of the copyright owner.